STUDI EKSPERIMENTAL PERILAKU SAMBUNGAN BALOK-KOLOM PRACETAK BETON AGGREGAT KASAR RINGAN - Herawan, Rudy
Abstract: The experimental research is conducted to study the behavior of external and internal subasemblages of precast concrete beam-column using lightweight coarse aggregate concrete made from peletized fly ash. The object of the research are two specimens of exterior and interior beam-column subasemblages with the same compressive strength and precast beam and column dimension. Those exterior and interior beam-column subasemblages were tested under quasi-static cyclic reverse loading at the top of column. The behaviour observed in this experimental study is the reliability of joint, in which the requirement of reliabel joint is the stability of strength and stiffness and also the ability to dissipate energy at the designed level of ductility. Experimental result show that the designed joint system has sufficient reliability until the ductility level of u=4. From the aspect of joint stress reduction factor, exterior beam-column subasemblage has a better stiffness than the interior subasemblage. This is because of the anchorage of beam rebars in exterior joint is longer than those in interior joint due to narrower space in panel joint.